Ecos das invasões napoleónicas na produção literária portuguesa em diálogo - Nascimento, Maria Teresa (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
The analysis of a set of dialogues published in Portugal during the troubled period of the French invasions, revealed the potential of the genre as an instrument of resistance against the invader through criticism, laughter, derision, but also via the role of encouragement to manifestations of a patriotic nature. Dialogue, which had not lost its vitality since the appearance of Ropicapnefma in 1532, now seems to clearly take a Lucianesque direction.